2000
DOI: 10.1034/j.1600-0692.2000.d01-24.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis of inclusions in Ti‐deoxidised steels

Abstract: The precipitation of non‐metallic inclusions in Ti‐deoxidised steels is analysed with the multiphase equilibrium code CEQCSI which is based on the IRSID slag model. For that purpose, the slag model has been extended to systems containing titanium oxides, using data available in the literature, and validated with industrial results obtained on various steel grades. Applications concerning slag‐metal reactions in ladle metallurgy are described. 2 applications concerning inclusions in Ti‐deoxidised steels are als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 5 publications
3
59
0
Order By: Relevance
“…Because it is much more expensive than aluminum, it is usually added after Al deoxidation in order to minimize Ti losses through reaction with oxygen. Several authors [39][40][41] have investigated inclusion compositions after Ti/Al deoxidation using sampling techniques, but no comprehensive equilibrium measurements for Ti/Al deoxidation have been conducted. Kunisada et al 42) reported that in the case of Ti/Al deoxidation the oxygen content in liquid steel is lower than in the case of Ti deoxidation but is higher than in the case of Al deoxidation; hence, there is no advantage of Ti/Al deoxidation for reducing oxygen content compared with Al deoxidation.…”
Section: Addition Of Ti Alloying Elementmentioning
confidence: 99%
“…Because it is much more expensive than aluminum, it is usually added after Al deoxidation in order to minimize Ti losses through reaction with oxygen. Several authors [39][40][41] have investigated inclusion compositions after Ti/Al deoxidation using sampling techniques, but no comprehensive equilibrium measurements for Ti/Al deoxidation have been conducted. Kunisada et al 42) reported that in the case of Ti/Al deoxidation the oxygen content in liquid steel is lower than in the case of Ti deoxidation but is higher than in the case of Al deoxidation; hence, there is no advantage of Ti/Al deoxidation for reducing oxygen content compared with Al deoxidation.…”
Section: Addition Of Ti Alloying Elementmentioning
confidence: 99%
“…When calcium-iron alloy is added to the melt, alumina can react with calcium to form CaO·6Al 2 O 3 as shown in Eq. (14). This reaction is determined by linear combination from Eqs.…”
Section: Thermodynamic Calculation Of Al-ti-ca-o Complex Inclusionsmentioning
confidence: 99%
“…21) Until now, the researchers haven't reached an agreement on the equilibrium phases of the Al-Ti-O system in molten steel yet. Ruby-Mayer et al 14) and Jung et al 15) insisted that there was a liquid stable region between Al 2 O 3 and Ti 3 O 5 regions based on thermodynamic calculation. However, Wang et al, [9][10][11] M-A Van Ende et al 12) and Matsuura et al 16) thought that only Al 2 O 3 , Ti 2 O 3 , Ti 3 O 5 , and Al 2 TiO 5 were stable phases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermodynamics for Al deoxidation or Ti deoxidation reaction have been studied well, while the complex deoxidation by Al and Ti addition has not been comprehensively understood. Ruby-Meyer et al 1) have estimated the Fe-Al-Ti-O equilibrium phase diagram by employing the multiphase equilibrium code CEQCSI based on the IRSID slag model 2) The stability of non-metallic inclusions containing titanium in solid steel would be more complex due to the formation of nitride, carbide and so on, which are normally not found at high temperatures. The behavior of non-metallic inclusions in solid state steel is quite important to understand the relationship between microstructure of steel and mechanical properties, and thus to maximally bring out such properties for best performance.…”
Section: Introductionmentioning
confidence: 99%